Catheter Ablation of Atrial Fibrillation in Patients with Mechanical Mitral Valve: Long‐Term Outcome of Single Procedure of Pulmonary Vein Antrum Isolation with or without Nonpulmonary Vein Trigger Ablation. (19th May 2014) - BAI, RONG; DI BIASE, LUIGI; MOHANTY, PRASANT; SANTANGELI, PASQUALE; MOHANTY, SANGHAMITRA; PUMP, AGNES; ELAYI, CLAUDE S.; REDDY, YERUVA MADHU; FORLEO, GIOVANNI B.; HONGO, RICHARD; BEHEIRY, SALWA; RUSSO, ANTONIO DELLO; et al.
Long‐Term Outcome of AF Ablation in MMV Patients: Introduction: It is unclear whether extended pulmonary vein antrum isolation (PVAI) plus nonpulmonary vein (non‐PV) trigger elimination prevents more arrhythmia recurrence than PVAI alone in patients with mechanical mitral valve (MMV) undergoing AF ablation. This study compared the efficacy and long‐term outcome of 2 ablation strategies—PVAI alone versus extended PVAI plus non‐PV trigger elimination—for the treatment of AF in patients with MMV. Methods and Results: One hundred and nine consecutive AF patients with MMV were divided into 2 groups: standard PVAI was performed in group 1 (N = 45); in group 2 (N = 64) PVAI was extended to the LA posterior wall, LA septum, and CS; and all non‐PV triggers were eliminated. Patients were followed up for 3 years. At the 12th month, 7 (15.6%) patients in group 1, and 39 (60.9%) patients in group 2 were arrhythmia free (log‐rank P < 0.001). Four patients (8.9%; 3 cases of AT and 1 case of AF) from group 1, and 12 patients (18.8%; 9 cases of AT, and 3 cases of AFL) from group 2 experienced very late recurrence. At 36 ± 7 months follow‐up, the cumulative recurrence after a single procedure was 42/45 (93.3%) in group 1, and 37/64 (57.8%) in group 2 (log‐rank P < 0.001). Conclusion: Compared with the standard PVAI alone, a strategy including extended PVAI and non‐PV trigger elimination is associated with a higher 12‐month and long‐term arrhythmia‐free survival in patients with MMV undergoing AF ablation. Very late recurrence may occur years after the initial procedure with focal AT as the most common type of recurrent arrhythmia.